Relationship Between Mast Cell Density and Various Histological Features in Melanocytic Lesions - Lazarova, Blagica; Petrushevska, Gordana; Jashar, Dzengis; Stojanovska, Zdenka (Scripta Medica, 2025)
Background/Aim: Mast cells, derived from multipotent hematopoietic progenitors in the bone marrow, are immune cells typically found in varying concentrations within melanocytic lesions. Aim of this study was to investigate mast cell density (MCD) in 182 melanocytic lesions, with a particular focus on its association with demographic and histopathological characteristics.Methods: MCD and secondary changes in melanocytic lesions were assessed histopathologically using paraffin-embedded tissue samples analysed under a Nikon Eclipse E400 microscope.Results: MCD was significantly higher in lesions from females compared to males and in lesions located on the head and neck compared to those on the arm, trunk and leg. Nevi exhibited higher MCD than melanomas, with marked differences observed among specific lesion types. Histopathological analysis revealed that lesions devoid of clear cells and those exhibiting an angioadnexocentric pattern had significantly elevated MCDs. Furthermore, lesions characterised by prominent elastic fibres, mucin deposition and certain adjacent structural interactions demonstrated increased MCDs.Conclusion: These findings underscore the complexity of mast cell functions in melanocytic lesions, offering valuable insights that may enhance diagnostic and therapeutic strategies.